PENATALAKSANAAN FISIOTERAPI PADA PASIEN BRONKITIS DENGAN INFRA-RED DAN CHEST THERAPY DI WILAYAH KERJA PUSKESMAS RURUKAN - Tolu, Fiana; Geneo, Martinus (Lasalle Health Journal, 2022)
Background: Respiratory tract disorders are still the biggest problem in Indonesia. This can be seen from the high prevalence and morbidity due to respiratory and pulmonary diseases such as acute respiratory infections, tuberculosis, asthma and bronchitis. Chest physiotherapy is a physiotherapy method that is very beneficial for people with respiratory diseases, both acute and chronic. Objective: The purpose of this study was to determine the effect of infrared and chest therapy in reducing sputum in patients with bronchitis. Method: This study uses a case study approach to 1 (one) respondent by providing intervention (pre-post) infra red and chest therapy. This research was conducted at the Rurukan Health Center, East Tomohon District. Results: The results obtained were that there was a reduction in the patient's sputum after the intervention was performed 6 times. Conclusion: So it can be concluded that there is an effect of infrared and chest therapy in reducing sputum in patients with bronchitis.